SUB-LETHAL EFFECT OF ZINC INDUCED HISTOPATHOLOGICAL ALTERATIONS IN THE GILL, LIVER AND KIDNEY OF GOLDFISH, (CARASSIUS AURATUS) - A. Subburaj; T. Francis; P. Elakkanai; N. Jayakumar (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The present study was carried out to find out the histopathological alterations in gill, liver and kidney of Goldfish (Carassius auratus) under sublethal concentrations of Zinc. Fishes were exposed to sub-lethal concentrations of 0.572, 1.145, 2.289, 4.578 and 9.156 mg.l -1 for 28 days which are 1/10 of their 96hr LC. The histological samples of gill, liver and kidney were collected from 14 th, 50th and 28th day and stained by haematoxylin and eosin, observed under trinocular microscope. Vacuolation, hyperplasia, epithelial lifting and lamellar fusion, shrinkage of blood vessels, secondary lamellar damage, breakdown of epithelial cells, blood congestion and necrosis were observed in gill. Rupture of nucleus, congested blood vessels, hemorrhage in liver sinuses, increased size of kupffer cell, increased pycnotic nucleus, hypertrophied hepatocytes, vacuolation, cellular necrosis, rupture of hepatocytes were observed in liver of zinc treated fish. Shrunken glomerulus, vacuolation, blood congestion, increased in space of periglomerular, increased in space of peritubular, melanomacrophages, loss of cytoplasm, fat deposition, degenerated tubules and degenerated glomerulus were seen in kidney. The above results showed that sub-lethal toxicity of Zinc alter the internal organs of goldfish at lower concentration.